What does ex-post evidence tell us about the output effects of future tax reforms? - Richard Anthony Kneller; Florian Misch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper reviews the existing evidence on the effects of tax reforms on output levels and growth over the short and long run from different strands of the literature. It develops and applies criteria to evaluate the usefulness of ex-post estimates to predict the effects of tax reforms ex-ante. These include whether the estimated policy change can be replicated in practice and whether the estimates are reliable. Based on these criteria we present detailed tables summarizing and comparing ex-post estimates of the effects of tax reforms. Overall, our review suggests that at least the direction of the long-run growth effects can be predicted with a reasonable degree of certainty. However, our review also suggests that depending on the tax change, trade-offs between short-run stabilization and long-run growth may arise and that more research on this question is needed.
urn:nbn:de:bsz:180-madoc-31768
Keywords: E62; H20; O20; 330; Tax Reforms; Tax Policy; Aggregate Growth; Tax Multipliers; Fiscal Policy